海洋钙离子非保守行为及海洋钙问题 - 曹知勉; 戴民汉 (2008)
钙离子是海洋11种常量离子之一,与钠、钾等离子的保守性不同,钙离子在海洋中的分布表现出微小但系统的变化。钙离子的变化往往与海洋碳酸钙的形成和溶解过程有关,所以,钙离子可直接指示海洋碳酸钙通量(深层海洋碳通量的主要组成部分)。同时,碳酸钙沉淀或溶解又会改变总碱度和溶解无机碳,通过钙离子变化也能间接探讨海洋碳酸盐系统和海洋吸收CO2的能力。介绍了以碳酸钙溶解形成超额钙为主的海洋钙离子多种非保守行为及其控制过程,讨论这些过程对海水组成和海洋碳酸盐系统的影响,探讨未来海洋酸化条件下钙离子可能的变化及其潜在的效应,最后展望在南海开展钙离子精细行为的研究意义。 Dissolved calcium ion (Ca2+) is one of the eleven major ions in the ocean. Unlike the conservative ones, such as sodium ion (Na+) and potassium ion (K+), Ca2+ has small but systematic variations in the ocean, likely related to the formation and dissolution of calcium carbonate (CaCO3) particles. High precision measurements of Ca2+ can thus provide insights of CaCO3 cycling and fluxes. Moreover, due to the fact that CaCO3 precipitation and/or dissolution also affect the carbonate system, we can potentially link the Ca2+ variation to discuss the oceanic sink of atmospheric CO2. This paper attempts to summarize the reported excess Ca and other non-conservative calcium behaviors and to discuss their controlling processes and impacts on the seawater composition and the carbonate system. The potential changes and the role of Ca2+ in the context of ocean acidification are also touched upon. 国家自然科学基金创新群体科学基金项目“海洋生物地球化学过程与机制”(编号:40521003)资助